The Relationship Between Motivation and Worker’s Productivity in Civil Registration and Population Department, Asahan Regency, Indonesia - Ningsih, Supiah (Budapest International Research and Critics University, 2018)
Human resources as labor or employees play an important role in improving productivity and achievement of predetermined objectives. Efforts to mobilize labor are an important task for agencies. In this case the agency should be able to do coaching on employees so that they want to perform work activities effectively and efficiently. By conducting coaching on employees, will be obtained by qualified, competent, reliable, have high morale to achieve a goal that leads to work performance. The result of data analysis with multiple linear regression analysis method Y = 5.567 + 0,105X1 + 0,967X2 + 0,450X3 + 1,078X4 + 0,164X5 + e, it means that every improvement of motivation variable consist of X1, X2, X3, X4, X5 for one unit then it will also increase the productivity at the Department of Population and Civil Registration Kab. Asahan of 0.105, 0.967, 0.450, 1.078, and 0.164 units.